(untitled) (International Journal of Engineering and Computer Science, 2016)
Today’s interest in magnesium alloys for automotive applications is based on the combination of high strength properties and low density. For this reason magnesium alloys are very attractive as structural materials in all applications where weight savings are of great concern.The automobile engine connecting rod is a high volume production, critical component. It connects reciprocating piston to rotating crankshaft, transmitting the thrust of the piston to the crankshaft. Every vehicle that uses an internal combustion engine requires at least one connecting rod depending upon the number of cylinders in the engine. As the purpose of the connecting rod is to transfer the reciprocating motion of the piston into rotary motion of the crankshaft. Connecting rods for automotive applications are typically manufactured by forging from either wrought steel or powdered metal.The objective of this paper is to optimization and fabrication of connecting rod using Mg-alloy material. Forged steel used to manufacturing the connecting rod presently. Connecting rod is modeled in Solide Works V13.and Model will be imported in ANSYS 13 for analysis. After analysis results will be comparing with experimentally in terms of stress, strain and deformation.The material will be prepared with stir casting process and hot extrusion process